El Niño/Southern Oscillation-driven rainfall pulse amplifies predation by owls on seabirds via apparent competition with mice. Issue 1889 (24th October 2018) - Thomsen, Sarah K.; Mazurkiewicz, David M.; Stanley, Thomas R.; Green, David J.
Abstract : Most approaches for assessing species vulnerability to climate change have focused on direct impacts via abiotic changes rather than indirect impacts mediated by changes in species interactions. Changes in rainfall regimes may influence species interactions from the bottom-up by increasing primary productivity in arid environments, but subsequently lead to less predictable top-down effects. Our study demonstrates how the effects of an EL Niño/Southern Oscillation (ENSO)-driven rainfall pulse ricochets along a chain of interactions between marine and terrestrial food webs, leading to enhanced predation of a vulnerable marine predator on its island breeding grounds. On Santa Barbara Island, barn owls ( Tyto alba ) are the main predator of a nocturnal seabird, the Scripps's murrelet ( Synthliboramphus scrippsi ), as well as an endemic deer mouse. We followed the links between rainfall, normalized difference vegetation index and subsequent peaks in mouse and owl abundance. After the mouse population declined steeply, there was approximately 15-fold increase in the number of murrelets killed by owls. We also simulated these dynamics with a mathematical model and demonstrate that bottom-up resource pulses can lead to subsequent declines in alternative prey. Our study highlights the need for understanding how species interactions will change with shifting rainfall patterns through the effects of ENSO under global change.